Quality Enhancement in Higher Education: Insights from Strategic Plan Implementation - Azhar, Muh; Subaedah, Subaedah; Asykur, Muamar (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research aims to understand the role and impact of implementing strategic plans in improving the quality of education at Alauddin State Islamic University, Makassar. The research method used in this research involves a qualitative approach with data collection techniques in the form of in-depth interviews, observation and documentation studies. Data were analyzed using qualitative descriptive analysis techniques, with data reduction, presentation and verification processes. The validity of the data was verified through data triangulation techniques, ensuring the consistency and validity of the research results. The results of the research show that the implementation of strategic plans at the Faculty of Tarbiyah, Alauddin State Islamic University, Makassar, has a positive impact on improving the quality of educational institutions. The steps taken, such as SWOT analysis, operational policy updates, and collaboration between leadership and staff, contribute significantly to improving the quality of education. Alignment between strategic plans, institutional goals, and objectives and implementing standard operating procedures (SOP) encourages achieving effective and efficient work results. The implications of this research show the importance of implementing strategic plans in the management of educational institutions to improve the quality of education and provide better services to stakeholders.